Mitochondrial-Targeted Triphenylphosphonium–Hydroxycamptothecin Conjugate and Its Nano-Formulations for Breast Cancer Therapy: In Vitro and In Vivo Investigation - Kunfeng Zhang; Jingxin Fu; Xiaorui Liu; Yifei Guo; Meihua Han; Meifeng Liu; Xiangtao Wang (Pharmaceutics, 2023)
Mitochondria are involved in various stages of cancer cell diffusion and metastasis. Therefore, targeting tumor mitochondria with antineoplastic medicines to cause mitochondria to initiate apoptosis may be an effective strategy for cancer therapy. Here, in order to enhance the anti-tumor efficacy of the antineoplastic agent hydroxycamptothecin (HCPT), the mitochondrial targeting ligand 4-(carboxybutyl) triphenylphosphine bromide (TPP) was attached to HCPT by an ester linkage. The resultant TPP-HCPT (TH) conjugate could self-assemble into nano-aggregates, with a mean particle size of 203.2 nm and a polydispersity index (PDI) value of 0.312. The TH conjugate could also co-assembly with mPEG3000-PLGA5000 into nanoparticles (TH-NPs), with a mean diameter of 86.41 nm, a PDI value of 0.256 and a zeta potential of −0.125 mV. In contrast to HCPT injections, TH aggregates displayed enhanced cellular uptake, mitochondria-targetability and cytotoxicity against 4T1 cells, while TH-NPs showed even better improvement than TH aggregates. In the in vivo study, TH aggregates displayed higher anti-tumor efficacy in 4T1 tumor-bearing mice than HCPT injections (tumor inhibition rate, 55.71% vs. 69.17%), and TH-NPs displayed more superior anti-tumor effects (tumor inhibition rate, 80.02%). In conclusion, our research demonstrated that the TPP-HCPT conjugate and its nano-formulations, including TH aggregates and TH-NPs, may be a promising mitochondria-targeting anticancer medicine for cancer therapy. As far as we know, this is the first report in which TPP and HCPT have been conjugated directly for this aim.